Métodos de preparo dos músculos do assoalho pélvico para o parto - Alves, Priscila Godoy Januário Martins (2017)
Perineal trauma due to vaginal delivery is a risk factor for the development of pelvic floor dysfunction (PFD). Prenatal methods for preparing the pelvic floor muscles (PFM) for labor such as perineal massage, vaginal dilator Epi-No® and pelvic floor muscle training (PFMT) have been used as preventive measures for perineal trauma. In this way, two studies were developed. The first study aimed to elaborate an intervention protocol to compare the effects of the three preparation methods of the PFM in the prevention of perineal trauma, and the second study compared the effects of perineal massage, vaginal dilator Epi-No® and PFMT on the perineal integrity of primiparous women. Sixty-three single fetus primigravidae were included with age over 18 years and who wished to have a normal delivery. The evaluation of sociodemographic characteristics, obstetric data and function of the PFM by the PERFECT method was performed. After, participants were randomized into perineal massage group (PMG, n = 21), vaginal dilator group (VDG, n = 21) and PFMT group (PFMTG, n = 21). The techniques were practiced from 34 gestational weeks until delivery. After delivery, the perineal outcomes were assessed and it included the perineal integrity and the characteristics of perineal lacerations (type, location, shape and degree of perineal laceration), as well as the presence of suture and perineal pain. Labor and neonatal data were also collected. A reassessment of PFM function was performed between 45 and 60 days postpartum. The satisfaction with the use of the technique was verified by a structured questionnaire and the number of days of practice of the proposed technique and the degree of discomfort evoked by it was verified through an intervention diary. The results showed that there was no significant difference in the presence of perineal lacerations in the three groups. The PFMTG presented a significant presence of 2nd degree lacerations and episiotomy. The PMG presented higher values of the variables E, R and F after delivery. PMG considered that the technique was not easy to perform while the PFMTG presented less pain and discomfort complaints during the practice of the method. The VDG was the group which considered the technique practiced most unpleasant while the PFMTG considered that the technique helped to relax during delivery. It was concluded that PMG and VDG demonstrate similar effects in relation to perineal integrity and were superior to PFMTG. The post-partum PFM function verified by the P variable was similar between the groups, whereas the PMG presented better muscle condition in the E, R and F variables and the PFMTG presented a better degree of satisfaction in performing the technique, being less annoying to practice it.